2022
DOI: 10.1155/2022/3629373
|View full text |Cite|
|
Sign up to set email alerts
|

Double-Negative T Cells Attenuate Cisplatin-Induced Acute Kidney Injury via Upregulating IL-10/AT2R Axis

Abstract: Objective. Our previous research showed that TCR+CD4-CD8-double-negative (DN) T cells protect renal epithelial cells from cisplatin-induced acute kidney injury (AKI). Therefore, this study is aimed at investigating the mechanism underlying the effect of DN T cells against Cis-induced AKI. Methods. HK-2 cells cultured alone or with DN T cells were treated with or without Cis. After treatment, the cell viability and death were analyzed by a CCK-8 kit and flow cytometric assay with Annexin V/PI staining, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: The presence of these indicators undermines our confidence in the integrity of the article's content and we cannot, therefore, vouch for its reliability.…”
mentioning
confidence: 99%